Forgiveness Education in Fourth- through Eighth-Grade Classrooms: Development and Evaluation of a New Forgiveness Curriculum - Loren Toussaint; Angela Kueny; Allison Stevens (MDPI AG, 2024)
The purpose of this study was to examine the efficacy of a new middle-school-classroom forgiveness curriculum in promoting forgiveness and reducing anger. The students in this study were 153 fourth through eighth graders in three regional parochial schools. The students were assigned to forgiveness education or control groups in the fall semester and reassigned to the opposite group in the spring semester. Before-and-after assessments of forgiveness and anger were collected in both the fall and spring semesters. The quantitative results showed that levels of forgiveness increased as expected in both semesters, but anger did not change in expected ways. The qualitative results showed that the children's conceptualizations of the forgiveness process aligned closely with the core forgiveness curriculum content. The results suggest that meaningful work can be accomplished to promote forgiveness in the middle school classroom using this newly developed, efficient, and effective curriculum that can be implemented by teachers and staff.